Cover Picture: Dinuclear Ruthenium(II) Complexes as Two‐Photon, Time‐Resolved Emission Microscopy Probes for Cellular DNA (Angew. Chem. Int. Ed. 13/2014). Issue 13 (11th March 2014) - Baggaley, Elizabeth; Gill, Martin R.; Green, Nicola H.; Turton, David; Sazanovich, Igor V.; Botchway, Stanley W.; Smythe, Carl; Haycock, John W.; Weinstein, Julia A.; Thomas, Jim A.
<x xml:space="preserve">Abstract</x> Using two‐photon absorption ruthenium complexes that bind to nuclear DNA in fixed or living cells can be photoexcited within the biological optical window. In their Communication on page 3367 ff., J. A. Thomas and co‐workers show that the long‐lived 3MLCT emission of these "light‐switch" complexes (>100 ns) means that they are also phosphorescence lifetime imaging microscopy (PLIM) probes.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>